Relación entre complicaciones postoperatorias en cirugía de terceros molares y edad en pacientes atendidos en la Facultad de Odontología de Iquitos 2025 - Inuma Shapiama, Prisca Melina (2025)
Objective: To establish the relationship between postoperative complications in third molar surgery and age in patients treated at the Iquitos School of Dentistry in 2025. Method: A quantitative, non-experimental, correlational, cross-sectional, and retrospective study was conducted. The sample included 185 medical records of patients treated in 2025. The observational technique was used. The instrument used for this study was the data collection form for information analysis. This form was validated in a previous study, with a Kuder-Richardson coefficient of 0.801, confirming its validity and reliability. (4) Results: 90.8% of the sample had pain, and only 9.2% did not. The most common complication in the sample was swelling, with 61.2%, while 38.8% did not. Ninety-four percent of the sample presented complications, while only 5.3% did not. The highest percentage of both sexes presented complications, representing 94.7%. There is a relationship between age and complications in third molar extractions (p=0.004). Conclusions: This study concluded that 94% of the sample presented complications, while only 5.3% did not. There is a relationship between age and complications in third molar extractions (p=0.004).